Contested port hinterlands: An empirical survey on Adriatic seaports. Issue 2 (June 2017) - Acciaro, Michele; Bardi, Andrea; Cusano, Maria Ines; Ferrari, Claudio; Tei, Alessio
Highlights: The analysis focus on the study of the port hinterland contestability. The case study focus on North Adriatic Ports and their hinterland. Ports compete not only on the seaside but also on the landside. Both efficiency and not efficiency related factors are affecting NAPs competiveness. Results underline how non-efficiency related factors are strategic for the NAPs. Abstract: Ports compete not only on the sea-side (e.g. through terminal investments, increase in terminal efficiency, maritime service connectivity) but also on the land-side (e.g. through logistics chain, advanced IT services, door-to-door connectivity). On this issue, several studies (e.g. Meersman et al., 2009; Tongzon, 2009) recently pointed out the increasing importance of the connectivity – at both quality and quantity level – between the port and its own hinterland in order to be competitive in the modern maritime service structure. The analysis concentrates on the study of the port hinterland contestability and on the definition of the catchment area focusing on a case study (i.e. the Adriatic ports aiming at attracting the Southern German freight flows) in order to better understand which elements affect the possibility to expand the current ports' hinterland. The empirical research is based on public statistics (e.g. Eurostat, Amadeus database) and on data directly collected from the operators currently serving Southern German firms with the main commercial ports and with the potential port actors that may be interested in an enlargement of the port catchment area in the studied region (e.g. South European ports). Apart from the trade pattern analysis – based on the general statistics – and the logistics structure analysis – based on the information collected by transport and logistics operators –, a direct survey has been conducted on a sample of manufacturing companies located in Southern Germany and Western Austria in order to understand what actions should be taken in order to promote the use of Adriatic ports and then reshape the boundaries of the catchment areas of these ports. Statistical tools and a bottom-up approach have been developed in order to evaluate the results. Main findings are then related to potential strategies that may fill in the competitive gap between Northern and Southern European ports when they compete to serve the same hinterland. The original contribution of the research is an insight on the relative importance of the infrastructure endowment, the generalized transport cost and also of some non-monetary conditions – as cultural and behavioural aspects – that have an influence in determining the effective boundaries of ports' hinterland.